Tinjauan Momen Lentur Pelat Dua Arah dengan Metode Perencanaan Langsung dan Metode Elemen Hingga - Fahri, Muhammad; Suyadi, Suyadi; Purwanto, Eddy (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This research conducted to study and determine the bending moment plate by using the Direct Design Method and Finite Element Method. In the procedure of calculation of concrete structures for buildings, namely SNI 2847 2013 has been set up several plates planning methods one of which is a method of using the Direct Design Method analysis. Finite element method (FEM) is dividing a complex problem into small elements where a simpler solution can be easily obtained. The theory used in plate analysis with the FEM is Kirchhoff-Love theory in which the limits are used specifically for the analysis of thin plates with small deflections by ignoring the transverse shear forces. The program is used by applying the Finite Element Method in this study is a Microsoft Excel as a tool for calculations and modeling program SAP 2000 as a plate structure. From the calculations that the value of deflection and the bending moment on the plate two directions with varying results.From the results obtained show that the static moments of total factored Direct Planning Method and the Finite Element Method showed results equal to each other . Distribution moments on the foundation and interior plate field differently due to direct Planning Method using a great moment coefficients in pedestal while the Finite Element Method using transition stiffness matrix Keywords:Direct Design Method, Finite Element Method, Two way slab, SAP 2000